(untitled) (Bangladesh Journal of Child Health, 2022)
Background: HbA1c is now accepted as a standard measure for diagnosing type 2 diabetes mellitus. Maternal high HbA1c levels have been associated with increased risk of adverse neonatal outcomes. Objective: To find out the relationship between maternal HbA1c and neonatal outcomes. Materials & Methods: This prospective observational study was conducted from February 2018 to January 2019 in the Department of Neonatology and Department of Gynecology & Obstetrics, BSMMU, Dhaka. Diabetic mothers with known HbA1c Value and their infants who were born in this study period in BSMMU were enrolled. Neonates were divided into two groups. One group that had maternal HbA1c <6% and the other group >6%. Neonatal weights, routine capillary blood glucose were recorded. Results: Among the total 94 mothers, HbA1c level were <6% in 56 mothers and ³6% in 38 mothers. The mean weight, BMI and previous history of gestational diabetes of mothers were significantly higher in HbA1c ³6% group. Birth weight and large for gestational age infants was high in ³6% HbA1c group. Neonatal hypoglycemia developed more in high HbA1c group. Total visible birth defect was 4 and all were in high HbA1c group (p=0.022). Conclusion: Elevated HbA1c level during pregnancy is a predictor for large for gestational age infants as well as neonatal hypoglycemia. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 74-78